2023
DOI: 10.3389/fphar.2023.1082066
|View full text |Cite
|
Sign up to set email alerts
|

The current trend of exosome in epithelial ovarian cancer studies: A bibliometric review

Abstract: Background: Epithelial ovarian cancer (EOC) is the most common type of ovarian cancer. About 90% of ovary tumors are epithelial. The current treatment for EOC involves surgical debulking of the tumors followed by a combination of chemotherapy. While most patients achieve complete remission, many EOCs will recur and develop chemoresistance. The cancer cells can adapt to several stress stimuli, becoming resistant. Therefore, new ways to fight resistant cells during the disease are being studied. Recently, exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…They achieve this by containing proteins such as programmed death-ligand 1 (PD-L1), which interact with receptors on immune cells, suppressing their activity. Moreover, exosomes carry microRNAs regulating the expression of genes involved in immune function [ 138 ]. Additionally, cancer cells release exosomes promoting the activity of immunosuppressive cells like regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) [ 139 ].…”
Section: The Impact Of Tumor Derived Exosomes On Immune Suppression A...mentioning
confidence: 99%
“…They achieve this by containing proteins such as programmed death-ligand 1 (PD-L1), which interact with receptors on immune cells, suppressing their activity. Moreover, exosomes carry microRNAs regulating the expression of genes involved in immune function [ 138 ]. Additionally, cancer cells release exosomes promoting the activity of immunosuppressive cells like regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) [ 139 ].…”
Section: The Impact Of Tumor Derived Exosomes On Immune Suppression A...mentioning
confidence: 99%
“…These exosomes can contain proteins such as programmed death-ligand 1 (PD-L1) that interact with receptors on immune cells and suppress their activity [ 4 , 5 ]. Exosomes can also carry microRNAs that regulate the expression of genes involved in immune function [ 3 ]. Exosomes can promote the activity of immunosuppressive cells: Cancer cells can release exosomes that contain molecules that promote the activity of immunosuppressive cells such as regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs) [ 5 ].…”
Section: Exosomes and Their Impact On Immune Suppression And Cancer P...mentioning
confidence: 99%
“…Using bibliometric analysis, we can obtain the research status, hotspots, and future research directions in this field [ 18 ]. At present, bibliometric analyses of many oncology and immunology studies have emerged in an endless stream [ 19 , 20 ], which have played a guiding role in the research in corresponding fields and have enabled scholars to gain a deeper understanding of the development of each field. A literature search revealed that although there are many studies in the field of renal xenotransplantation, there is no corresponding bibliometric analysis of the trends, countries, authors, keywords, or citations in this field.…”
Section: Introductionmentioning
confidence: 99%